Measurements of heavy-flavour production in p-Pb collisions with ALICE: quark matter 2015 - Wilkinson, Jeremy (Nuclear physics. A, Nuclear and hadronic physics, 2016)
The production of open heavy-flavour particles was studied in p-Pb collisions at sNN=5.02 TeV using the ALICE detector. Three separate observables were used: the hadronic decays of D mesons at mid-rapidity, and semileptonic decays of heavy-flavour hadrons to electrons and muons at mid-rapidity and forward rapidity, respectively. The most recent ALICE measurements of the nuclear modification factor, RpPb, of open charm and beauty are reported, along with the centrality and multiplicity dependence of D-meson production in p-Pb collisions.